DISTRIBUTION OF SUBSIDIZED DIESEL FUEL ON FISHING VESSELS IN PPI LHOK BENGKUANG, SOUTH ACEH: Distribusi BBM Solar Subsidi pada Kapal Perikanan di PPI Lhok Bengkuang, Aceh Selatan - Thahir, Muhammad Agam; Berasa, Cukup Karina; Rizal, Muhammad; Akbardiansyah (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2023)
Fishers at PPI Lhok Bengkuang, South Aceh Regency, are still unable to obtain subsidized fuel oil. This is influenced by the increasing demand and the limited fuel supply at nearby fuel station.The purpose of this study is to calculate the amount of diesel fuel distributed to fishers, the servicecapacity of the fuel station at PPI Lhok Bengkuang, and the amount fuel supply. Data were collectedthrough observation and direct interviews with fishers who buy fuel regularly, which are then analyzedusing simple math. The results of this study show that 125 L of diesel fuel were subsidized subsidiesfor 4 months, with a monthly average requirement of 31.92 liters. Fishing vessels with a size of 1–10GT consumed most diesel fuel ranging from 85 to 285 liters. The tank capacity of the fuel station is20,000 liters, and to fullfil the demand, diesel fuel is delivered 1-2 times per month. Keywords: fishing vessels, fishing port Lhok Bengkuang, fuel, subsidized diesel